2015
DOI: 10.1590/2175-7860201566216
|View full text |Cite
|
Sign up to set email alerts
|

Novos registros em Tillandsia L. (Bromeliaceae, Tillandsioideae) para o Rio Grande do Sul, Brasil

Abstract: Resumo São registradas pela primeira vez para a flora do estado do Rio Grande do Sul (Brasil) Tillandsia loliacea Mart. ex Schult.f. e Tillandsia pohliana Mez, sendo também redescoberta Tillandsia bandensis Baker neste estado e Brasil. São fornecidas descrições, fotografias e dados de suas distribuições geográficas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…In this region, Büneker et al . (2015) registered T. bandensis only as a lithophyte species. We also observed that only T. tricholepis extends from the westernmost to the northern coastal plain, as Winkler (1980) and Gonçalves and Waechter (2003) noted.…”
Section: Discussionmentioning
confidence: 99%
“…In this region, Büneker et al . (2015) registered T. bandensis only as a lithophyte species. We also observed that only T. tricholepis extends from the westernmost to the northern coastal plain, as Winkler (1980) and Gonçalves and Waechter (2003) noted.…”
Section: Discussionmentioning
confidence: 99%
“…Nestas encostas, pequenos capões de mata se desenvolvem formando ambientes para espécies de caráter florestal como Anemia phyllitidis (figura 5e), Blechnum polypodioides (figura 2i), Adiantum raddianum (figura 5f) e Adiantopsis perfasciculata (figura 5c). Em angiospermas, novas ocorrências e espécies novas têm sido descritas com frequência para estas áreas, em vários grupos taxonômicos como Asteraceae (Mondin 2007), Bromeliaceae (Büneker et al 2015) e Poaceae (Welker & Longhi-Wagner 2012).…”
Section: Discussionunclassified
“…Tillandsia loliacea has a wide distribution, occurring in Argentina, Bolivia, Brazil, Paraguay, and Peru (Smith and Downs 1977). In Brazil, this species occurs in the states of Alagoas, Bahia, Ceará, Espírito Santo, Federal District, Goiás, Mato Grosso, Mato Grosso do Sul, Minas Gerais, Paraíba, Paraná, Pernambuco, Piauí, Rio Grande do Norte, Rio Grande do Sul, São Paulo and Sergipe, in Deciduous and Semideciduous Seasonal Forests, and in the forests located in the Pampa, Caatinga (stricto sensu), and Cerrado biomes (Büneker et al 2015, Flora do Brasil 2018. According to Fiorato (2009), T. loliacea occurs in rupestrian fields and Caatinga in northeastern Brazil, with epiphytic or rupicolous habit.…”
Section: Discussionmentioning
confidence: 99%